2012
DOI: 10.1103/physrevb.86.064505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ru substitution on electron correlations and Fermi-surface dimensionality in Ba(Fe1xRux)

Abstract: We report a systematic angle-resolved photoemission spectroscopy study on Ba(Fe1−xRux)2As2 for a wide range of Ru concentrations (0.15 ≤ x ≤ 0.74). We observed a crossover from twodimension to three-dimension for some of the hole-like Fermi surfaces with Ru substitution and a large reduction in the mass renormalization close to optimal doping. These results suggest that isovalent Ru substitution has remarkable effects on the low-energy electron excitations, which are important for the evolution of superconduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
24
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
(33 reference statements)
4
24
1
Order By: Relevance
“…We show that there are no significant changes either in electronor hole-like FSs upon substantial Ru substitution and this observation is consistent with the observations of Dhaka et al [20]. But at about 50% doping there is significant change in the hole-like FSs which is also consistent with the experimental findings by N. Xu et al [25]. We study the nature of FSs when doped in any of the three sites mentioned above through first principles simulations.…”
Section: Introductionsupporting
confidence: 93%
“…We show that there are no significant changes either in electronor hole-like FSs upon substantial Ru substitution and this observation is consistent with the observations of Dhaka et al [20]. But at about 50% doping there is significant change in the hole-like FSs which is also consistent with the experimental findings by N. Xu et al [25]. We study the nature of FSs when doped in any of the three sites mentioned above through first principles simulations.…”
Section: Introductionsupporting
confidence: 93%
“…We observe clear L modulations of the spin excitation intensities at both 2.5 meV and 6 meV. The K z dependence of the band structure revealed by ARPES further confirmed the 3D nature of the system [13,14]. We notice that the dynamical spin correlation lengths in this sample are much shorter than that characterizing the spin wave excitations in the ordered parent compounds [20][21][22][23].…”
supporting
confidence: 77%
“…The same measurements also find that the electron and hole Fermi surfaces are reasonably well nested over the whole phase diagram with Ru doping, in contrast to the carrier doped systems [13,14]. More interestingly, Hall and ARPES measurements have shown that the mobility of the carriers and the Fermi velocities in BaðFe 1Àx Ru x Þ 2 As 2 increase dramatically as compared with those of BaFe 2 As 2 , indicating that the electron-electron interactions are further reduced under Ru doping [13].…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Angle-resolved photoemission spectroscopy (ARPES) measurements report no change in the shape of the Fermi surface and Fermi velocities up to x ¼ 0.55 [29] while other ARPES studies find a crossover from two-to three-dimensional geometry of some holelike pockets of the Fermi surface accompanied by the mass increase for the larger doping levels x [30]. These results were theoretically analyzed in a recent ab initio study [31].…”
mentioning
confidence: 92%